تحليل الإمكانيات الكارتوغرافية لمرئيات القمر الصناعي QUICKBIRD - ديوب وائل (Latakia University Journal -Engineering Sciences Series, 2018)
The availability of high-resolution imagery, such as QUICKBIRD ones, has made the satellite imagery a possible alternative to the conventional aerial mapping. In this paper, we discuss the possibilities to produce large scale topographic maps by using QUICKBIRD images, in terms of semantic content and geometric precision. The analysis of the semantic content was done in a theoretical and practical way using the process of image interpretation, and the semantic scale of the topographic map that can be produced from the QUICKBIRD images, was derived. As for the geometric precision, it was discussed theoretically and the resulting map scale was then derived from the accuracy of QUICKBIRD image rectification. This rectification was achieved by the help of a set of control points. Finally, the geometric precision of the image was analyzed visually via an overlapping of the rectified image with a topographic map of a 1/1000 scale to evaluate the values ​​of the displacements. As a result, it was found that it is possible to produce maps withe scale 1/10000 which is suitable for semantic content as well as for geometric precision of QUICKBIR images. إن توفر المرئيات الفضائية ذات دقة التمييز المكانية العالية , مثل مرئيات القمر الصناعي QUICKBIRD, قد فتح الأفق لاستخدامها في إنتاج الخرائط الطبوغرافية كبديل عن الصور الجوية. نناقش في هذا البحث إمكانيات رسم الخرائط الطبوغرافية ذات المقاييس الكبيرة من مرئيات QUICKBIRD وذلك من ناحيتي المحتوى الدلالي والدقة الهندسية. تم في البحث تحليل المحتوى الدلالي للمرئيات بطريقة نظرية وأخرى عملية وذلك باستخدام عملية تفسير الصور وتم استنتاج المقياس الدلالي للخارطة الطبوغرافية التي يمكن إنتاجها من المرئيات QUICKBIRD. أما فيما يخص الدقة الهندسية, فقد تمت مناقشتها من الناحية النظرية ومن ثم تم استنتاج مقياس الخارطة المنتجة من المرئية QUICKBIRD من خلال دقة عملية إرجاع هذه المرئيات باستخدام مجموعة من نقاط الضبط. تم أخيراً تحليل الدقة الهندسية للمرئية بشكل بصري عبر مراكبة المرئية المرجعة مع مخطط طبوغرافي مقياسه 1/1000 وذلك لتقييم قيم الانزياحات. نتيجة لهذه التحليلات, تم التوصل إلى أنه من الممكن إنتاج خرائط من المقياس 1/10000 وهو مقياس يعبّر عن المحتوى الدلالي وكذلك عن الدقة الهندسية للمرئيات QUICKBIRD.